2007
DOI: 10.3233/jad-2007-11203
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics Analysis of the Alzheimer's Disease Hippocampal Proteome

Abstract: Alzheimer's disease (AD) is characterized by the presence of intracellular neurofibrillary tangles (NFT), extracellular senile plaques (SP), and synaptic loss. The hippocampus is a region that plays an important role in memory and cognitive function, and it is severely affected in AD. The levels of proteins in the hippocampus may provide a better understanding of the pathological changes known. In the present study we used two-dimensional gel electrophoresis and mass spectrometry techniques to determine change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
148
6
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 216 publications
(169 citation statements)
references
References 79 publications
14
148
6
1
Order By: Relevance
“…Due to its involvement in glycolytic pathway, carbonylation, and reported decreased expression and activity of PGM1 in the AD brain compared with the age-matched controls are consistent with the loss of total cellular energetics in AD (362). Taken together, oxidative inactivation of these ATP-related enzymes may be related to known metabolic defects in AD detected by PET scanning (309,317).…”
Section: Identification Of Carbonylated Proteins In Brainsupporting
confidence: 53%
“…Due to its involvement in glycolytic pathway, carbonylation, and reported decreased expression and activity of PGM1 in the AD brain compared with the age-matched controls are consistent with the loss of total cellular energetics in AD (362). Taken together, oxidative inactivation of these ATP-related enzymes may be related to known metabolic defects in AD detected by PET scanning (309,317).…”
Section: Identification Of Carbonylated Proteins In Brainsupporting
confidence: 53%
“…The overall increase in ferritin seems to exceed that of iron, at least in the hippocampus of AD patients, hence most iron should be ferritin-bound (Galazka-Friedman et al 2004), thus in a safe state. Interestingly a quantitative analyses of isoferritins in the brain of controls and AD patients found region and disease specific alteration of the balance between H and L subunits, with the L subunit concentration being lower in the cortex and in the SN of AD brain (Connor et al 1995); a proteomic analysis of AD hippocampi also found elevated H-chain levels (Sultana et al 2007). As observed in different experimental systems, this imbalance could be associated with an abnormal iron management by ferritin itself.…”
Section: Ferritin In Brain Disorders With Altered Iron Homeostasismentioning
confidence: 90%
“…We, and others, have also demonstrated the potential for this approach in identifying neurodegenerative-specific changes in postmortem brain tissues. Using subproteome studies, constituents of isolated amyloid plaques (18), AD hippocampus (19), cortical Lewy bodies (20), AD membrane fraction (21), and specific phosphorylation sites in neurofibrillary tangles (22) were identified. Using broader discovery proteomics, we demonstrated unique candidate proteins in both AD (23,24) and FTLD-U (25).…”
mentioning
confidence: 99%